STRATEGI KOMUNIKASI KONSELING DALAM MENANGANI PERMASALAHAN AKADEMIK MAHASISWA - Satya Candrasari (Professional: Jurnal Komunikasi dan Administrasi Publik, 2020)
The world of education is very important in shaping one's character, so in a college there needs to be a bureau that handles counseling guidance issues, in order to help students who have academic problems that can hamper their studies. Good communication in counseling is an absolute thing that must be mastered and understood by the counselor. This research uses a qualitative method with a descriptive approach. The results of this study are counseling communication strategies carried out by counselors that is focused on the problems faced by students (person secentered). The stages of counseling communication carried out are conducting initial observations or interviews, interviews or counseling processes, and ending counseling by psychological assessment. Keywords: counseling communication, college student, communication strategy, student academic problems, student counseling bureau.